Limits of institutional reform in development: changing rules for realistic solutions - Andrews, Matt (New York, 2013)
This book emerged in response to mounting evidence that institutional reforms in development often do not work. Case studies and multicountry analyses show that many governments in developing nations are not becoming more functional, even after decades and hundreds of millions of dollars of externally sponsored reforms. These studies increasingly suggest that disappointing results cannot be explained by routine excuses, either. One cannot simply blame governments in these countries for not doing reforms, because many governments remain deeply dysfunctional even after many satisfactorily completed projects introducing best practices advocated by international organizations. The work on institutional reform in develop ment has seldom explored reasons for failure beyond such excuses, however. This has created a gap in the literature, which is important from academic and practical perspectives. The academic challenge is to see if theory and evidence can help promote a better understanding of why many reforms do not lead to better governments. The practical imperative is more fundamental: Can a better understanding of past experience help improve the likelihood of more institutional reform success in more developing countries in the future? Driven by these questions, the book seeks to provide a product that is useful to academics and practitioners in the development field. It combines ideas from various streams of institutional theory to ana lyze a diverse set of institutional reform experiences. This analysis yields an argument that reforms are limited when governments adopt them as signals to garner short-term support. Such reforms are often unrealistic; they may produce new laws that make governments look better, but these are seldom implemented and governments are not really better after the reforms. The analysis points to examples where reforms are not simply adopted as signals, however, and have helped make governments more functional. These experiences inform an alternative approach to doing institutional reform called problem-driven iterative adaptation (PDIA), which yields realistic reforms that actually produce better governments over time.